ASSESMENT OF AWARENESS ABOUT MALOCCLUSION AMONG PATIENTS – A QUESTIONNAIRE STUDY - MONISHA.P.KHATRI C.R.R.I; S.P.SARAVANA DINESH (International Journal of Pharma and Bio Sciences, 2014)
A questionnaire study was done to assess the awareness of malocclusion among patients visiting a private college in Chennai. It contained eight questions that could assess the patients knowledge about malocclusion, problems associated with it and initiative taken to visit an orthodontists to get it treated. It was distributed to 300 patients (n=300). After computing the data, it was observed that in spite of having the basic understanding about malocclusion people refrained from visiting an orthodontist to get it treated. Therefore it is necessary to carry out programs that would help the population to understand malocclusion and its complications better and take initiative to visit an orthodontist to get the problem treated.